Constraints and Motivation behind Jute Cultivation (Indian Journal of Extension Education, 2009)
Jute is an important cash crop of poor farmers of West Bengal. Productivity of jute is low as compared to achievable yield potential due to several reasons. The study was, therefore, conducted to identify constraints and motives of jute cultivation by the farmers in eight villages of three districts viz., North 24-Parganas, Nadia, and Hooghly of West Bengal with total 144 respondent farmers from different categories. The data were collected with the help of pre-tested semi-structured interview schedule and participatory rural appraisal (PRA) tool. The results reveal that more than 80 per cent of farmers are unaware about the improved production technologies due to lack of appropriate regularized market and grading system (93%) followed by huge labour required for performing manual retting operation of jute (81 %) and high wages of labour during peak season (79%). Non availability of good quality water (42%) and insufficient water bodies for retting (28%) and irrigation are also reported and confined their severity on the basis of rank based quotient value. However, the farmers are cultivating jute to get the jute sticks for domestic fuel and utilize their family labourers, despite, getting low or no economic returns. A multi-prong strategic effort of research and development with emphasis on strengthening extension system is essentially needed for jute development.